Natural learning in the South African context: A critical analysis - Ramroop, Renuka Suekiah (University of Limpopo, 2019)
The Natural Learning Approach (NLA), commonly referred to as ‘unschooling’, is deeply embedded in the belief that children have an innate desire to learn. Therefore, the notion of autonomy and freedom of the learner in the learning and living process is highly valued and the cornerstone of this approach. The home and the child’s broader environment become the authentic space for the unfolding and implementation of the NLA, where learning and living is a seamless experience. This study examined how the individual and the family go about creating their unique ‘curriculum’, how learning happens, and how families negotiate the challenges of this approach. Using a mixed methods research design, a questionnaire was used to collate quantitative data, and a sample of ten families (parents and children) and seven young adults contributed to the qualitative data; documents were also used as part of the qualitative strand. Content, thematic and critical analysis were used to analyse the data to gain and provide a deeper understanding of this phenomenon. The research evidence of this study evinced that diverse, vibrant, holistic and joyful learning is taking place in the NLA homes. Families shared how authentic learning took place when children directed their own learning process and where the diversity of each unique human individual is valued and empowered. Furthermore, the study attested the key role of the parents in the child’s development and wellbeing. Possibilities of how this approach can be extended to broader society under the notion of a learning society is also proposed. Recommendations and further research suggestions are outlined so that possibilities of the NLA becoming the key learning approach to birth a vibrant learning society in South Africa is realised.
Thesis (PhD. Ed. (Curriculum Studies) --University of Limpopo, 2019
Keywords: Natural learning; South Africa; Context; Distance learning; Education, Elementary; Education